2015
DOI: 10.4070/kcj.2015.45.5.364
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of the Serum Apurinic/Apyrimidinic Endonuclease 1/Redox Factor-1 in Coronary Artery Disease

Abstract: Background and ObjectivesApurinic/apyrimidinic endonuclease 1/redox effector factor-1 (APE1/Ref-1) is a multifunctional protein involved in the DNA base excision repair pathway, inflammation, angiogenesis, and survival pathways. We investigated serum APE1/Ref-1 in patients with coronary artery disease (CAD).Subjects and MethodsSerum APE1/Ref-1 was measured with a sandwich enzyme-linked immunosorbent assay from 360 patients who received coronary angiograms. They were divided into two groups; a control (n=57) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…In the current study, we observed that in the tumor tissue, APE1 protein, an essential DNA repair enzyme in the BER pathway, could be a promising predictive biomarker for the responses of NSCLC patients receiving platinum-containing chemotherapy. Moreover, this previously reported nuclear protein was detected in the serum of NSCLC patients, and its level in the serum was directly correlated with the level measured in cancer tissue [12, 16, 17]. In addition, we describe herein, for the first time to our knowledge, that alteration of sAPE1 after chemotherapy is significantly associated with response and PFS of platinum-containing chemotherapy.…”
Section: Discussionsupporting
confidence: 63%
“…In the current study, we observed that in the tumor tissue, APE1 protein, an essential DNA repair enzyme in the BER pathway, could be a promising predictive biomarker for the responses of NSCLC patients receiving platinum-containing chemotherapy. Moreover, this previously reported nuclear protein was detected in the serum of NSCLC patients, and its level in the serum was directly correlated with the level measured in cancer tissue [12, 16, 17]. In addition, we describe herein, for the first time to our knowledge, that alteration of sAPE1 after chemotherapy is significantly associated with response and PFS of platinum-containing chemotherapy.…”
Section: Discussionsupporting
confidence: 63%
“…In STEMI, inflammatory cells are functionally activated [25, 26]. After PCI, functionally active neutrophil infiltration is aggravated locally in the balloon-injured arteries [27].…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al found that the levels of APE1/Ref-1 were higher in serum from patients with coronary artery disease than in the serum from control patients. 24 Recently, it has been reported that plasma or urine APE1/Ref-1 levels significantly increase in bladder cancer patients; the area under the curve analysis showed diagnostic values with high specificity and sensitivity. 25 26 Although the underlying mechanisms for secreted APE1/Ref-1 are yet to be fully delineated, a few reports have been able to provide some insight into its biological functions.…”
Section: Extracellularly Secreted Ape1/ref-1 As a Potential Biomarkermentioning
confidence: 97%